THE EFFECT OF ISLAMIC WORK MOTIVATION AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE: A STUDY ON CV AGNI MANDIRI APPAREL - Laila Tafida, Adha; Utomo, Budi (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2026)
This study examines the influence of Islamic work motivation and career development on employee performance, with job satisfaction as an intervening variable at CV. Agni Mandiri Apparel. This study used quantitative methods, collecting data through questionnaires distributed to all 110 employees using a saturated sampling technique. Data analysis included validity tests, reliability tests, classical assumption tests, statistical tests, and path analysis using SPSS. The results showed that Islamic work motivation had no significant effect on employee performance, while career development had a positive and significant effect. Islamic work motivation and career development had a positive and significant effect on job satisfaction. Job satisfaction had no significant effect on employee performance. Job satisfaction was unable to mediate the effect of Islamic work motivation or career development on employee performance. This study concluded that improving employee performance at CV. Agni Mandiri Apparel is more effectively achieved through structured career development than through job satisfaction as an intermediary.